2001
DOI: 10.1007/s11745-001-0760-2
|View full text |Cite
|
Sign up to set email alerts
|

A single oral administration of conjugated linoleic acid enhanced energy metabolism in mice

Abstract: We investigated the effect of a single oral administration of conjugated linoleic acid (CLA) on energy metabolism in mice. Male Std ddY mice were orally administered CLA (5 mL/kg weight) or linoleic acid (5 mL/kg weight) (both solutions at concentrations of 73.5%) as a control. Oxygen consumption was significantly greater in the CLA-administered mice than in the control mice. Respiratory quotient was slightly lower in the CLA-adminis-tered mice than in the control mice. We calculated fat and carbohydrate oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 14 publications
(19 reference statements)
4
35
0
1
Order By: Relevance
“…Moreover, rats fed mixed CLA isomers produced lower respiratory quotients, 85 indicating increased oxidation in the body. These results, together with other studies, 11,40,44 suggest that CLA increases fat oxidation.…”
Section: Conjugated Linoleic Acid and Obesitysupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, rats fed mixed CLA isomers produced lower respiratory quotients, 85 indicating increased oxidation in the body. These results, together with other studies, 11,40,44 suggest that CLA increases fat oxidation.…”
Section: Conjugated Linoleic Acid and Obesitysupporting
confidence: 86%
“…It was also reported that dietary CLA at a level as low as 0.25% effectively elevated energy expenditure and subsequently decreased white fat pad mass in male Std ddY mice. 44 A recent study in Balb-C mice showed higher energy expenditure, excretion and heat loss when animals were fed a diet containing 0.93% CLA. 23 West et al 12 compared the increase of energy expenditure with the reduction of fat deposition and found that the increased energy expenditure was sufficient to account for the decreased adipose deposition in CLA-treated mice.…”
Section: Conjugated Linoleic Acid and Obesity Yw Wang And Pjh Jonesmentioning
confidence: 99%
“…In mice, however, CLA was observed to increase energy expenditure. 4,9,12 Also here, the discrepancy between animal and human studies might be caused by differences in metabolic rate. 30 …”
Section: Discussionmentioning
confidence: 86%
“…11 Furthermore, CLA intake has been associated with an increased energy expenditure. 4,9,12 Only a few human studies have been conducted to study the effect of CLA on body weight, body mass index (BMI) and/or fat mass. Even though fat mass 13,14 and sagital abdominal diameter 15 were lowered by CLA, it did not result in body weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators found reduced body weight after a CLA diet (West et al, 1998;DeLany et al, 1999;Park et al, 1999a), whereas others found no effect (Park et al, 1997, Park et al, 1999bWest et al, 2000;Miner et al, 2001;Sisk et al, 2001) or an increase in body weight (Miner et al, 2001). Furthermore, CLA supplementation is associated with an increased energy expenditure (West et al, 1998(West et al, , 2000Ohnuki et al, 2001). The results of studies on the effects of CLA on energy intakes are inconsistent.…”
Section: Introductionmentioning
confidence: 99%